Optimal orientation and tilting angle of pv panels considering shading and temperatute effects - Chong, Boon Yoong (2023)
The optimal orientation and titling angle of the photovoltaic (PV) panels are crucial for maximizing their energy output and ensuring a great return on the investment for solar power systems. This report investigates the crucial relationship between optimal orientation, tilting angle, shading, and module temperature in the context of PV output performance. The main objective is to determine PV panels' optimal orientation and tilting angle to maximize energy generation while considering shading and temperature effects. The investigation location is at Universiti Tunku Abdul Rahman (UTAR), Bandar Sungai Long. Three transposition sky models, converting global horizontal irradiance to global tilted irradiance, are utilized and compared to estimate global tilted irradiance, while a simple 2-D trigonometric approach is proposed for calculating the shading factor. The conventional Ross coefficient model is used to predict the module operating temperature and its impact on PV performance. The results show that the optimal tilting angle of PV array depends on the DL (distance between two rows of PV array to the panel length) ratio and panel configuration, considering shading effects with bypass diodes. The optimal surface azimuth angle is slightly South of due East (104°- 122°). Although the temperature effect does not significantly impact the optimal PV positioning, it does decrease the Reduced Equivalent Solar Irradiation due to Temperature Effect (RESIT) yielded in all directions. The suggested DL ratio is around 1.3 with the landscape 4-stacked configuration to minimize shading and loss. This study hopes to provide the solar industry with a guideline for installing PV panels at optimal orientation and tilting angles while considering shading and temperature effects to yield maximum PV output in Malaysia.